Cyclical Asset Returns in the Consumption and Investment Goods Sector - Burkhard Heer; Alfred Maußner; Bernd Süssmuth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We document the empirical fact that asset prices in the consumption-goods and investment-goods sector behave almost identically in the US economy. In order to derive the cyclical behavior of the equity returns in these two sectors, we onsider a standard two-sector real-business cycle model with habit formation and sector-specific adjustment costs of capital. The model is able to replicate the equity premium and the Sharpe values observed empirically. In addition, we are able to match the empirical fact that equity returns in the two sectors are not correlated with output.
Keywords: E32; G12; C68; 330